2011
DOI: 10.4081/ijas.2011.e41
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between hypoosmotic swelling test and breeding soundness evaluation of adult Nelore bulls

Abstract: This study aimed at evaluating the relationship between physical and morphological semen features with the hypoosmotic swelling (HOS) test in raw semen of adult Nelore bulls classified as sound and unsound for breeding. Two hundred and six Nelore bulls aging from 3 to 10 years of age were subjected to breeding soundness examination. After physical and morphological semen examination, HOS test was done. After the breeding soundness examination, 94.2% of the bulls were classified as sound for breeding. There was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
1
6
1
Order By: Relevance
“…In the current study, 20 and 53% prevalence of clinical and subclinical mastitis was noted in cattle, whereas it was 11 and 66% in buffaloes belonging to different areas of Khyber Pakhtunkhwa. This prevalence of subclinical mastitis was quite higher than the previous reports of 35% subclinical mastitis in cattle of district Muzaffar Gharr ( 14), 30% in cattle of district Lahore (9), and 44% in Punjab (11), and our previously reported 42% subclinical mastitis in buffaloes of district D. I. Khan (10). This considerable increase in the prevalence of bovine mastitis is alarming, which might be because dairy farming is rapidly growing in Khyber Pakhtunkhwa, and it is reported that mastitis is significantly increasing with an increase in the number of dairy animals (10).…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…In the current study, 20 and 53% prevalence of clinical and subclinical mastitis was noted in cattle, whereas it was 11 and 66% in buffaloes belonging to different areas of Khyber Pakhtunkhwa. This prevalence of subclinical mastitis was quite higher than the previous reports of 35% subclinical mastitis in cattle of district Muzaffar Gharr ( 14), 30% in cattle of district Lahore (9), and 44% in Punjab (11), and our previously reported 42% subclinical mastitis in buffaloes of district D. I. Khan (10). This considerable increase in the prevalence of bovine mastitis is alarming, which might be because dairy farming is rapidly growing in Khyber Pakhtunkhwa, and it is reported that mastitis is significantly increasing with an increase in the number of dairy animals (10).…”
Section: Discussioncontrasting
confidence: 76%
“…Mastitis is one of the most prevalent diseases of dairy animals all over the world (1), including Pakistan (11,14,15). In the current study, 20 and 53% prevalence of clinical and subclinical mastitis was noted in cattle, whereas it was 11 and 66% in buffaloes belonging to different areas of Khyber Pakhtunkhwa.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…The maximum sperm swelling was found as an indication of high fertility during the same study. However, Martins et al, (2011) found that even though there were significant differences in physical and morphological aspects of semen between highly fertile and poorly fertile bulls, no difference was found in the mean percentage of reactive sperm in HOS test.…”
Section: Hos Positive Sperm Percentage and Pregnancy Ratementioning
confidence: 83%